The effects of population density and lake characteristics on growth and size structure of brook trout Salvelinus fontinalis (Mitchill, 1815) in boreal forest lakes in Canada. (29th May 2017) - van Zyll de Jong, M.; Adams, B.; Cote, D.; Cowx, I.
Summary: This paper examines the effect of lake characteristics on population density and how this variation affects growth, mortality and population size structure of brook trout, Salvelinus fontinalis . The study was conducted on 17 recreationally fished, reproductively isolated boreal forest lakes in Newfoundland, Canada from 1993 to 2000. A standardized sampling program, the Fyke Littoral Index Netting program (FLIN) was used to collected data that describes brook trout population parameters and life history attributes. Regression analyses showed significant relationships between fish density and biomass and characteristics of the lakes. Variation in fish density and biomass was explained by lake surface area and littoral habitat area. Significant relationships were found when growth, mortality and size structure were regressed against density. The proportional stock distribution and theoretical maximum size of brook trout were negatively related to density, and natural mortality was positively related to density. The largest maximum length and highest proportional stock densities occurred at brook trout densities of less than 30 fish/ha. In general, the higher the proportion of littoral habitat area the higher the densities of brook trout, which correspondingly had important effects on growth, natural mortality and size structure of the brook trout populations. This information is critical to the development of management strategies aimed at altering size distribution to produce specific fisheries management outcomes.